Design and experiment of the bionic disc cutter for kenaf harvesters - Tian, Kunpeng; Zhang, Bin; Ji, Aimin; Huang, Jicheng; Liu, Haolu; Shen, Cheng (International Journal of Agricultural and Biological Engineering, 2024)
Aiming to ease the cutting of kenaf stalks via bionics, the bionic disc cutter was designed. The upper jaw of the Batocera horsfieldi was used as a bionic prototype. Further, to explore its dynamic performance, an indoor multi-stalk cutting experimental bench was used to simulate the field operation process. A three-factor and two-level interaction orthogonal experiment was carried out; cutting speed, stalk conveying speed (machine forward speed), and blade type (ordinary disc cutter and bionic disc cutter) were used as experiment factors. The cutting pass rate and cutting specific energy consumption were selected as evaluation indexes. The range, variance, and fuzzy comprehensive evaluation analysis were carried out on the experiment results. Moreover, the main order factors affecting the bionic cutter performance were determined-blade type, conveying speed, the interaction between the cutter speed and conveying speed, and cutter speed. The optimal parameter combination scheme had a cutter speed of 1000 r/min, conveying speed of 0.4 m/s, and included bionic blades. Under this condition, the best index was the 92% cutting pass rate, with a specific energy consumption of 4.38 J/stalk. The variance analysis has shown that, with 95% confidence, the blade type has a rather significant influence on the comprehensive index. Additionally, the conveying speed also significantly influenced it, while other factors and interactions had no notable effect. The experimental comparison under the same working condition shows that the bionic blade has better cutting effect. This study provides a reference for the development of cutter and the selection of kenaf harvester operational parameters.Keywords: kenaf harvester, bionic, disc cutter, orthogonal experiment, interactionDOI: 10.25165/j.ijabe.20231606.7997Citation: Tian K P, Zhang B, Ji A M, Huang J C, Liu H L, Shen C. Design and experiment of the bionic disc cutter for kenaf harvesters. Int J Agric & Biol Eng, 2023; 16(6): 116–123.